Drivers and Potential Consequences of Observed Extreme Hypoxia Along the Canadian Pacific Continental Shelf. Issue 6 (15th March 2023) - Franco, Ana C.; Ianson, Debby; Ross, Tetjana; Hannah, Charles; Sastri, Akash; Tortell, Philippe D.
Abstract: Bottom waters of the northeast Pacific continental shelf naturally experience localized hypoxic conditions, with significant influences on food webs and biogeochemical cycling. In August 2021, extreme hypoxia was detected from several measurement platforms along the southern British Columbia continental shelf, with oxygen concentration <60 μmol kg −1, and a difference from the seasonal climatology of more than 2 standard deviations. Early and intense remote upwelling and local density shifts were associated with an anomalously strong spring phytoplankton bloom, which likely stimulated localized respiration of subsurface organic matter. This event was concurrent with unsuitable habitat for Pacific halibut and calcite and aragonite undersaturation throughout most of the water column. The drivers of this extreme low oxygen event could be enhanced under future climate change, with potentially significant impacts on marine ecology and biogeochemistry. Plain Language Summary: Most marine organisms consume oxygen, and are therefore impacted when seawater oxygen concentrations reach low values. Extreme low oxygen concentrations are rare in the coastal waters of British Columbia, Canada. However, unusually strong oxygen depletion was observed off the coast of Vancouver Island during summer 2021. Unusually strong, early season upwelling winds along the California coast impacted Vancouver Island by causing nutrient‐rich water to be mixed into the surface, stimulating a large and earlier than usual spring phytoplankton bloom. Decomposition of the bloom‐derived organic carbon consumed local subsurface oxygen throughout the spring and summer. These subtle changes in timing and intensity of seasonal processes likely caused this low oxygen event, which was also associated with high concentrations of inorganic carbon, leading to ocean acidification. Such extreme low oxygen events, even if short‐lived, can have a significant impact on marine ecosystems, restricting the habitat available for groundfish species, such as Pacific halibut, and impacting the formation of carbonate shells by various organisms. The drivers of extreme low oxygen events are projected to intensify as climate change progresses. Key Points: Widespread extreme hypoxia was observed throughout the water column along the southern British Columbia continental shelf in summer 2021 Early and intense upwelling followed by a strong biological response contributed to oxygen depletion in subsurface waters Multiple indices suggest that this extreme event was concurrent with unsuitable habitat conditions for groundfish and calcifying organisms